IMPLEMENTASI KOMUNIKASI TERAPEUTIK TERHADAP KEPATUHAN DIET PADA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS MACCINI SAWAH MAKASSAR - Syah Thalib, Abdul Herman; Tasik Bula (Bina Generasi : Jurnal Kesehatan, 2025)
Diabetes mellitus is a term that describes a metabolic disease characterized by high blood sugar levels in the blood (hyperglycemia), in which diabetes mellitus sufferers experience an increase. Research objective: to determine the implementation of therapeutic communication on dietary compliance in type two diabetes mellitus patients. Research method: The design used in this research is a case study report. This case study was conducted on two respondents who suffered from type 2 diabetes mellitus with Inclusion Criteria Patients willing to be respondents, Patients with composmentis awareness, Patients who suffer from type 2 diabetes mellitus, Age 45-70 and Exclusion Criteria Patients with diabetes mellitus who cannot communicate, Type 1 gestational diabetes mellitus and Outpatients. Research results: Based on the results of measuring the level of diet compliance in respondents I and II, on the first day, respondent 1 experienced an increase in blood sugar levels of 282 and respondent 2 experienced an increase in blood sugar levels of 208 and after communication regarding treatment of diet compliance, blood sugar levels decreased. Conclusion: it can be concluded that the application of therapeutic communication to dietary compliance in type 2 diabetes mellitus patients can improve their diet compliance.